2020
DOI: 10.3390/ani10112175
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Safe Inclusion of Narbonne Vetch (Vicia narbonensis) in Rainbow Trout (Oncorhynchus mykiss) Diets: Towards a More Sustainable Aquaculture

Abstract: Aquaculture’s sustainability deeply relies on the identification and inclusion of alternative raw materials. Although meals from insects and/or byproducts from different industries are being recently tested, the meal from terrestrial vegetable species is still the main substitution candidate for fish meal. Here the effects of 0% (Control), 10% (A10) and 30% (A30) inclusion of Narbonne vetch (Vicia narbonensis; ZV-156 strain) meal in rainbow trout (Oncorhynchus mykiss) diets was assessed in a 63-day feeding tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 75 publications
(109 reference statements)
0
9
0
2
Order By: Relevance
“…Moreover, survival rate at the end of the experiment was 4-5-fold lower compared to previous experiments with gilthead seabream at mouth opening, reared at similar conditions [38,59]. The larvae survival when weaning is started at mouth opening is usually lower when compared to a late weaning in older larvae (16)(17)(18)(19)(20)(21)(22), that can vary between 11-56% [60][61][62]. However, it was similar among treatments, implying that curcumin supplementation had no effect on the observed survival rates.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Moreover, survival rate at the end of the experiment was 4-5-fold lower compared to previous experiments with gilthead seabream at mouth opening, reared at similar conditions [38,59]. The larvae survival when weaning is started at mouth opening is usually lower when compared to a late weaning in older larvae (16)(17)(18)(19)(20)(21)(22), that can vary between 11-56% [60][61][62]. However, it was similar among treatments, implying that curcumin supplementation had no effect on the observed survival rates.…”
Section: Discussionmentioning
confidence: 54%
“…All treatment showed a significant positive correlation between feeding incidence and larvae ag (CTRL-p = 0.002; LOW-p = 0.019; HIGH-p = 0.010, Figure 2). (5,6,8,12,16,20,23, and 28 days after hatching, DAH) fed experimental diets (CTRL, LOW, and HIGH). Values are expressed as mean ± SD.…”
Section: Feeding Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the present study a lower GC number was found in both PI and DI of fish fed FM0 diet. A reduction in GC might denote an immunosuppression in rainbow trout fed diets without FM, such has been shown in previous studies carried out on rainbow trout fed PP for 63 days [ 83 ]. Goblet cells maintain the epithelial homeostasis through the secretion of a mucosal barrier that acts as a lubricant, preserving the epithelium, although some studies support that GC can act as a major cellular component of the innate and adaptative defense system [ 84 ].…”
Section: Discussionmentioning
confidence: 69%
“…Rainbow trout (Oncorhynchus mykiss) are native to tributaries of the Pacific Ocean in Asia and North America, and have been introduced worldwide for sport fishing and commercial aquaculture [1]. Currently, they are one of the most largely farmed fish species worldwide (>848,000 t y), the biggest in the European (185,316 t) region and the second most common species produced in Spain (18,955 t) [2]. Salmonids evolved in natural systems with considerable environmental complexity and, as such, can exhibit numerous behavioral options in response to environmental challenges [3].…”
Section: Introductionmentioning
confidence: 99%